Strategi Inovatif Pemasaran Digital Berbasis Media Sosial untuk Peningkatan Omset Warkop Gasskeun - Adjie Wongso Moerdyanto; Mesra Betty Yel; Sutisna Sutisna (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service project aims to transform the conventional marketing model of Warkop Gasskeun, an MSME in the culinary sector, through systematic digital marketing strategies to enhance visibility and sales revenue. The primary problem identified was the lack of digital asset utilization and the absence of customer data analysis, which kept market reach confined to a narrow geographical radius. The methodology followed a System Development Life Cycle approach, covering market requirement analysis, content architecture design, digital platform implementation (Instagram, TikTok, and Google Business Profile), and performance evaluation based on digital metrics. Key innovations included: (1) Local SEO to improve location indexing on search engines; (2) Business Insights features as a practical Business Intelligence instrument to read audience behavior and demographic preferences; and (3) consistent product information across all digital platforms. Outcomes showed measurable growth in audience interaction and content reach, which directly corresponded with increased physical customer visits and a stronger digital customer database for future promotional decisions. The findings confirm that social media technology, when managed through an information systems approach, can build a real competitive edge for MSMEs in today's digital economy.